Reesa vespulae - Majka, Christopher G. (Zenodo, 2007)
Reesa vespulae (Milliron, 1939) NOVA SCOTIA: Halifax Co.: Halifax, 7.v.1981, 13.v.1981, 21.v.1981, 15.vi.1981, 1.v.1983, and 24.v.1983, B. Wright, (25), NSMC; Halifax, 14.i.1991, R. Grantham, (2), NSMC; Lake Egmont, 20.vi.1990, E. Parker, NSMC. PRINCE EDWARD ISLAND: Queens Co.: Charlottetown, 4.vii.1986, 1.viii.2000, and summer 1998, M.E.M. Smith, (7), ACPE; Charlottetown, 1.vii.1986, L.S. Thompson, ACPE. Newly recorded in Nova Scotia (Fig. 3). Found in the northern states in the USA (Beal 2003); in Canada recorded across the country from British Columbia and the Northwest Territories east to Newfoundland. A minor pest of insect and plant collections, occasionally found in granaries and dwellings (Bousquet 1990). In natural circumstances it is a scavenger of dead insects and spiders in wasp nests (Beal 1967). : Published as part of Majka, Christopher G., 2007, The Derodontidae, Dermestidae, Bostrichidae, and Anobiidae of the Maritime Provinces of Canada (Coleoptera: Bostrichiformia), pp. 1-38 in Zootaxa 1573 (1) on page 16, DOI: 10.11646/zootaxa.1573.1.1, http://zenodo.org/record/5096635 : {"references": ["Beal, R. S., Jr. (2003) Annotated checklist of Nearctic Dermestidae with revised key to the genera. The Coleopterists Bulletin, 57 (4), 391 - 404.", "Bousquet, Y. (1990) Beetles associated with stored products in Canada: an identification guide. Agriculture Canada Research Branch, Ottawa, Ontario. Publication 1837, 1 - 215.", "Beal, R. S., Jr. (1967) A revisionary study of the North American dermestid beetles formerly included in the genus Perimegatoma. Miscellaneous Publications of the Entomological Society of America, 5, 281 - 312."]}